Characterization of micro-crystalline lead tungstate with different morphologies produced by the sonochemical process - Kaowphong S. (2014)
Micro-crystalline PbWO4 was sonochemically produced using Pb(CH3COO)2 • 3H2O and Na 2WO4 • 2H2O in aqueous solutions with and without anionic surfactant (sodium dodecyl sulphate or sodium lauryl sulphate). The product morphologies were influenced by the pH values and the surfactant. Micro-crystalline PbWO4 composing of Pb, W and O, and W-O stretching vibration band of WO4 tetrahedrons were detected using XRD, SEM, EDX, TEM, SAED and FTIR. Photoluminescent intensities, caused by the electronic transition from 1T2 to 1A1 states, shown to increase with the increase in the pH values of the solutions. © 2010 Pleiades Publishing, Ltd.